MENGINISIASI PERUBAHAN PENDIDIKAN SEBAGAI BENTUK KESIAPAN DIRI BANGSA INDONESIA SEBAGAI BAGIAN DARI MASYARAKAT EKONOMI ASEAN (Sebuah resensi terhadap buku berjudul: Planning for Educational Change: Putting people and their contexts first) - Zidniyati Zidniyati (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2015)
This writing is a review of a book entitled ‘Planning for educational change: putting people and their contexts first’. In the book written by Martin Wedell which was published in 2009 by Continuum International Publishing Group, London, explained some fundamental issues that should be done and need to take into account (a) whether it needs to do changing in national educational system, (b) what are things need to be done before deciding to do changing in the national educational system, and (c) what are the affect and impact of the educational change. In the book written in 185 pages, it was founded very clear and deep explanation to be learned by people who concern in education and policy makers in Indonesia. In addition, Indonesia as a developing country has lots in common things with some countries from which Wedell took as examples of other developing countries with their educational change. Having read the book review, it is expected to appear some accurate consideration right before and during an implementation of change. Because of Wedell gave some results of his research of educational change in some developing countries around the world, it will offer lots of advantageous contribution to people concerning in education and policy makers in Indonesia as one of developing country which has educational system that is possibly continuing to be changed anytime, especially at the beginning of Indonesia declared as part of Economic ASEAN Community.